Stylin': The Great Masculine Enunciation and the (Re)Fashioning of African Diasporic Identities. Issue 3 (4th May 2017) - Checinska, Christine
ABSTRACT: In this article, Christine Checinska aims to: (i) outline the carnivalised theoretical approach that characterises her analysis of African diasporic cultural expressions, (ii) explore the creolised aesthetic that shapes the styling—or stylin', in colloquial terms—adopted by African diasporic men in the Caribbean, and (iii) to posit the notion of stylin' as a creolised non-verbal Nation Language (a term coined by Kamau Brathwaite; see History of the Voice . London: New Beacon, 1984). In this schema, the (re)fashioning of the body facilitates the reconfiguration of diasporic identities that are in constant flux as a result of geographical, psychological, and social border crossings. The Haitian Revolution (1791–1804) is central to the discussion, since it arguably galvanised what the author calls "the Great Masculine Enunciation", a form of democratisation of dress that marked the shift from the functional, anonymous (un)dress of enslaved Africans to the elegant, embellished, individualised swagger of African diasporic peacock males. This constituted the reverse of the Great Masculine Renunciation in the West, which saw the abandonment of adornment in favour of understatement in fashionable male dress after the French Revolution (1789–1799), as described by J. C. Flugel ( The Psychology of Clothes . London: Hogarth, 1966).